Heritage, politics and identity : exploring the political manipulation of heritage in Zimbabwe - Tevera, Genius (My University, 2015)
Postcolonial Zimbabwe is currently in an era characterised by discursive contestations. This has seen the ruling party, ZANU PF, engaging in severe discourse manipulation in a bid to gain political legitimacy. This new era has resulted in the emergence of what Ranger (2004) has termed ‘patriotic history’, which is a new form of narrow history, which is biased towards celebrating an exaggerated role played by ZANU PF in liberating Zimbabwe, portraying the ruling party as the only truly legitimate rulers of post-independence Zimbabwe. This study, therefore,seeks to examine recent discourse on ZANU PF’s ideology, and to explore how this master narrative has been used to justify ZANU PF’s unpopular projects, such as the land reform programme, and the establishment of the National Youth Service ,popularly known as ‘Border Gezi youth camps’.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts in the field of Heritage Studies